Investigação da associação de polimorfismos nos genes TLR3, IFR5, TLR7 e TLR8 com a proteção contra febre Chikungunya, dor crônica e infecção assintomática - Gotay, Wilker Jose Perez (2024)
The Chikungunya virus (CHIKV), after being inoculated into the body through the bite of mosquitoes of the genus Aedes sp., causes an infection that leads to the activation of the innate antiviral immune response. This begins through the activation of pattern recognition receptors (PRRs), such as Toll-like receptors (TLRs) and consequent activation of the interferon regulatory transcription factor (IRF), which culminates in the production of antiviral molecules, such as type I interferons. Several factors, including host genetic variations and immune response against CHIKV, result in different clinical manifestations of the disease. Infection can range from subclinical to debilitating arthralgia and chronic inflammatory rheumatism. The present study aimed to investigate the association of single nucleotide polymorphisms (SNPs) in genes encoding the receptors TLRs-3 (rs3775291), TLR-7 (rs3853839) and TLR-8 (rs3853839) and in the gene encoding the factor of IRF5 transcription in susceptibility to CHIKV infection and development of persistent pain. To this end, a case-control study was carried out in the city of Fortaleza/CE, Brazil, with collection of data samples and samples during the years 2019, 2020 and 2021. The study included 121 cases with positive anti-CHIKVIgG serology, 29 asymptomatic cases (IgG anti-CHIKV +) and 182 healthy controls (IgG anti- CHIKV-) matched by age and sex. Polymorphisms were identified using TaqMan® SNP genotyping assays. The G polymorphic allele of the 3ʼUTR C/G variant (rs3853839) of the TLR7 gene and the G polymorphic allele of the 129 C/G variant (rs3764879) of the TLR8 gene were associated with protection against CHIKV infection(adjusted OR = 0.64; p = 0.02 and adjusted OR = 0.54; p = 0.001, respectively). These variants were also associated with pain in patients with chronic Chikungunya (adjusted OR = 0.54; p = 0.008 and adjusted OR =0.42; p = 0.002, respectively). Furthermore, individuals who presented the G allele in the rs3764879 variant had a greater chance of developing the infection in asymptomatic form (adjusted OR =2.88; p =0.004). Linkage disequilibrium (LD) analyzes for the SNPs rs3764879 and rs3853839 showed strong linkage disequilibrium between these markers (D'=0.99 and r2 = 0.98). No significant differences were observed for the 1234 C/T (rs3775291) variants of the TLR3 gene and 198 G/T (rs2004640) of the IRF5 gene in relation to the association with infection and chronic pain. Thus, the present study identified that polymorphisms in the TLR7 and TLR8 genes can act as protective factors for CHIKV infection and pain reduction, suggesting that these variants may play a role in the pathogenesis of Chikungunya.